Problem-Based Learning and Differentiated Instruction in Elementary Mathematics: A Systematic Literature Review of Students’ Problem-Solving (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This systematic literature review aims to analyze research trends related to the implementation of Problem-Based Learning (PBL) and Differentiated Instruction (DI) in elementary mathematics education, particularly in relation to students’ problem-solving abilities. Method: The review followed the PRISMA protocol by systematically searching the Scopus database. From 92 identified records, 24 empirical studies published between 2021 and 2024 met the inclusion criteria. The selected studies were analyzed based on research design, instructional approach, and problem-solving focus.. Results: The findings indicate that both PBL and DI independently contribute positively to students’ mathematical problem-solving skills, including reasoning, strategy development, and higher-order thinking. However, most studies examined PBL and DI separately, while only a limited number explicitly integrated both approaches within a single instructional framework. Novelty: This review highlights a significant research gap regarding the explicit integration of PBL and DI in elementary mathematics learning, emphasizing the need for instructional models that simultaneously address problem-centered learning and learner diversity.